PENGARUH KUALITAS PRODUK DAN HARGA TERHADAPKEPUTUSAN PEMBELIAN DAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Study Kasus Pada Mahasiswa FEB Universitas Islam Malang Yang Mengkonsumsi Mie Instan) - Khoiriatun Nafilah; Agus Widarko; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACConsumers buy products meet their wants and needs, but when the customer feels that their needs and desires have been met by the product offered by the company, it increases the intention of reprposing intention. In this study the variables used are products and prices. high prices will be much faster in earning profits, but here it will also be difficult to reach consumers. Research uses questionnaires which are distributed directly to the object of research, namely FEB students from Malang Islamic University who consume instant noodles. From a population of 3,040 students, only 97 students were taken to be used as samples which were tested using a partial test and a sobel test. From the results of this study, it is known that product quality and prices have a direct effect on purchasing decisions, product quality and prices have a direct effect on buying interest, buying interest directly influences purchasing decisions, buying interest can mediate product quality variables on purchasing decisions, and buying interest can mediate the price variable on the purchase decision.Keywords:Product Quality, Price, Purchase Decision, Buying Interest